Drug related harm reduction in the eu and candidate countries - success and gaps - Martin Busch; Alexander Grabenhofer-Eggerth; Charlotte Klein; Di Marion Weigl (Epidemiology, Biostatistics and Public Health)
Background: Evaluation of the state of play of the 2003 Council Recommendation on the prevention and reduction of health-related harms, associated with drug dependence, in the EU and candidate countries and elaboration of proposals for new recommendations. Methods: Analysis of epidemiological data available at the European Monitoring Center for Drugs and Drug Addiction (EMCDDA) using statistical modeling, a general literature review on harm reduction measures, four systematic literature reviews (one on peer naloxone pro-grams) and surveys among decision makers in the field of drug policy and among harm reduc-tion providers (“stakeholders”) using online questionnaires and a gap survey among the na-tional focal points of EMCDDA in EU-countries and candidate countries. Results: It was possible to decrease the number of HIV-infections among drug users substan-tially in most EU countries and candidate countries during the last decade; unfortunately for the numbers of deaths due to overdoses this effect could not be reached. Stakeholders (harm reduction providers) name improvement of needle and syringe exchange and harm reduction in prison as main priorities in order to reduce drug related infectious diseases. Concerning re-duction of mortality they prioritise peer naloxone programs, drug consumption rooms and first aid training of drug users.  Conclusions : The increase of coverage of substitution treatment and of the availability of nee-dle exchange programs in most countries can be seen as successes of harm reduction policy although the coverage especially of the latter still needs improvement. Peer naloxone pro-grams and improvement of harm reduction in (and after) prison are two of 13 recommended actions to improve the situation concerning mortality of opioid users. Continuous political strengthening of harm reduction is necessary.